By reducing TGF ?1, octreotide lessens the peritoneal derangements induced by a high glucose solution - Günal, AI; Duman, S; Sen, S; Ünsal, A; Terzioglu, E; Akçiçek, F; Basci, A (Wichtig Editore, 2001)
Background. Chronic peritoneal dialysis may eventually result in peritoneal fibrosis, which progressively reduces dialytic efficacy. Although the pathogenesis has not been elucidated, it has been proposed that transforming growth factor beta-1 (TGF beta1) plays a central role in the onset of peritoneal fibrosis. Methods. Rats were divided into three groups and given saline, hypertonic peritoneal dialysis solution alone, a hypertonic peritoneal dialysis solution plus octreotide intraperitoneally. After four weeks, a one-hour peritoneal equilibration test was done. Dialysate-to-plasma urea ratio, glucose reabsorption, ultrafiltration volume and levels of dialysate protein, TGF beta1 and cancer antigen 125 (CA 125) were determined. The peritoneal membrane was examined histologically by light microscopy. Results. Compared to the saline group, peritoneal function tests (ultrafiltration volume 6 (5-7) vs 0.0 ml, dialysate-to-plasma urea ratio 0.51 vs 0.76, glucose reabsorption 0.54 vs 0.40 and morphology (thickness 4.5 vs 75.5 mum) were dramatically deranged in hypertonic peritoneal dialysis solution-treated rats, which also had a higher level of TGF beta1 and undetectable CA 125. In contrast, in hypertonic peritoneal dialysis solution plus octreotide rats' peritoneal function was protected (ultrafiltration volume 3 mL, dialysate-to-plasma urea 0.60, glucose reabsorption 0.51) but peritoneal thickening (37.7 mum) was not so markedly reduced although the production of TGF beta1 was significantly inhibited. Conclusion. These data show that by inhibiting the production of TGF beta1, octreotide can preserve peritoneal function and remodeling of the mesothelial cell. Although the production of TGF beta1 was significantly inhibited, peritoneal thickening cannot be completely prevented.
Keywords: CAPD; peritoneal fibrosis; TGF beta-1; CA 125; octreotide